2018
DOI: 10.26495/rtzh1810.428337
|View full text |Cite
|
Sign up to set email alerts
|

Disfuncion Erectil: Prevalencia, Factores De Riesgo Y Actitudes en La Provincia De Chiclayo 2017

Abstract: Objetivos: Determinar la prevalencia de Disfunción Eréctil (DE), valorar la DE según dominios del Índice Internacional de Función Eréctil (IIEF-15), analizar los factores de riesgo de DE y ponderar las actitudes frente a la DE en varones de la provincia de Chiclayo. Métodos: La investigación es de tipo observacional y transversal. Se utilizó una Ficha de recolección datos con preguntas cerradas especialmente diseñadas y validadas por expertos. La técnica fue la entrevista de pacientes ambulatorios que acudían … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
0
3
0
1
Order By: Relevance
“…En Cuba H. contortus constituye el parásito de mayor prevalencia e incidencia, que limita seriamente el desarrollo de la ganadería ovina (Arece & López, 2013). Estudios en el país muestran un 73,8 % de prevalencia en la provincia Las Tunas (Medina, 2019).…”
Section: Isbnunclassified
“…En Cuba H. contortus constituye el parásito de mayor prevalencia e incidencia, que limita seriamente el desarrollo de la ganadería ovina (Arece & López, 2013). Estudios en el país muestran un 73,8 % de prevalencia en la provincia Las Tunas (Medina, 2019).…”
Section: Isbnunclassified
“…Erectile dysfunction (ED) is defined as the inability or significant reduction in men’s ability to achieve or maintain a penile erection with sufficient duration or rigidity for sexual activity, persisting over a period of at least several months and causing clinically significant distress, despite the desire for sexual activity and adequate sexual stimulation. 1 It is one of the most common sexual issues in men of all sexual orientations, 2 including men who have sex with men (MSM), in whom the impact can be even more significant. 3 A review found that 24% of MSM exhibited ED.…”
Section: Introductionmentioning
confidence: 99%
“…Although there is extensive evidence documented on the prevalence and factors associated with ED and PE, 3 these have not been specifically conducted in the MSM population, especially not in Latin America. 2 , 5 , 19 Additionally, prior studies have not investigated if variables such as the age at the onset of the first sexual relationship, 3 history of sexually transmitted diseases (STDs), 4 condom use frequency, 20 number of sexual partners, 21 and relationship duration 22 are related to ED and PE, leading to information bias. 2 Prior studies have had nonstandardized indicators of sexual dysfunction by not specifying which dysfunction is referred to, 2 have been descriptive in focus, 2 have not estimated the association measure under multivariate models, 23 and have enrolled a limited number of MSM participants, leading to a lack of statistical power.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation